Macroanatomy of Cecum in German Mast Geese (Anser Anser) and Investigation with Scanning Electron Microscope (Sem) - Baygeldi, S. B.; Guzel, B. C.; Ilgun, R.; Ozkan, E. (Facta-Fundacio Arnco Ciencia Tecnologia Avicolas, 2023)
Our study aimed to compare the cecum of German mast geese with other poultry species through macroanatomy and scanning electron microscope (SEM). Adult German geese were used as research material, which were obtained from its breeders and died of various causes. In the study, after determining the macroanatomical features of the German mast goose cecum, it was examined with a scanning electron microscope (JEOL JSM-5600LV) and the general structures were photographed. The craniodorsal of the rectum of German mast geese was shaped with two ceca, giving right and left arms to the cranial symmetrical to each other near the end of the ileum. The macroanatomy of the apex, corpus, and basis cecum parts was examined in the cecum divided into two. In the study, it was determined that villus extensions were sparse in the right and left apex ceci parts in the cecum SEM images of the German mast geese, while the number of the corpus and basis ceci parts was higher. As a result, the macroanatomy and scanning electron microscopic findings of German mast geese cecum were examined in detail and its differences from other poultry species were revealed.
Keywords: Anatomy; Digestive system; Embden goose; SEM